Obtención de alcohol etílico a partir del almidón de banano (Cavendish gigante) en la provincia de El Oro, El Guabo, 2014. - Espinoza Alvarado, Segundo V. (2015)
This research describes the technology used for the production of ethyl alcohol from starch banana, as well as variables to determine which treatment is achieved further amount of ethyl alcohol after fermentation. The variables studied were the percentage of starch in the suspension and time of hydrolysis with the enzyme these two variables were selected because they directly affect the amount of formed sugars (Brix), which are used by the yeast to convert into ethyl alcohol and carbon dioxide.